Use of Medicinal Plants in Monterrey, Mexico - Armando Enrique GONZÁLEZ-STUART (Notulae Scientia Biologicae, 2010)
Mexico has a rich tradition in medicinal plant use within its diverse traditional healing practices. Many people have used medicinal herbs to treat a variety of diseases and ailments for many generations. Located in the northeast, Monterrey is Mexico’s third largest city and one of the most industrialized cities in Latin America. In spite of widespread use of modern pharmaceuticals, and the availability of "scientific" or mainstream medicine in this city, many people still rely on traditional healers, as well as the use medicinal plants to combat illness. This study was undertaken in order to obtain information regarding the most popular medicinal plants used in Monterrey, as well as their uses, forms of application, and origin. Thirteen herbal providers voluntarily accepted to be interviewed within 2 of the city’s largest popular herbal marketplaces. A questionnaire written in the Spanish language was provided to all interviewees, regarding their years in business, their source of information or expertise in recommending herbs, as well as the type of herbs employed for the treatment of various diseases or afflictions. Fifty-six medicinal plants belonging to 27 botanical families, mostly sold as crude herbs, were mentioned by the herbal providers as being the most commonly used to treat various ailments.